Water Resources Potential and Development in Marathwada Region (Maharashtra State -India) (Global Journals of Research in Engineering, 2022)
Maharashtra is the second highest populated third largest in area and the second most industrialized state in India The state of Maharashtra came into existence on 1st May 1960 The Geographical location of the Maharashtra is bounded between latitude 16 40 to 22 10 N and longitude 72 60 to 80 90 E As per 2011 census the total population of Maharashtra is 112 37 Million which is 9 29 of the India s population 1210 19 Million The State has the geographical area of 0 307 Million Sq Km which is about 9 4 per cent of the total area of India The average rainfall of the State is approximately 1360 mm The maximum rainfall about 88 per cent occurs in four months between June to September about 8 per cent between October to December and remaining 4 per cent after December Further rainfall is ranging from 400 mm to 6000 mm in different parts of the State It is revealed from this that there is significant variation in rainfall distribution and its occurrence The State witnesses frequent drought conditions Almost 42 5 area of the State is drought prone